SPATIAL THINKING ABILITY IN ELEMENTARY SCHOOL - Herawati Herawati; Mimi Hariyani (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
Spatial thinking ability is the ability to mentally manipulate and rotate an object in solving two-dimensional and third-dimensional geometric problems as well as the ability to imagine the shape of an object from a different perspective in solving three-dimensional geometric problems. This spatial ability is very necessary for students because good spatial abilities will also support good understanding of mathematics. Apart from that, students also need spatial abilities to solve everyday problems, such as looking at a map, explaining their position and so on. This spatial ability consists of spatial visualization, spatial rotation and spatial orientation. To improve spatial abilities, teachers must be creative in designing learning by using various media or teaching aids that are appropriate to the material being studied.Keywords: Spatial thinking skills, Geometry, Elementary education